(3cJGH GdVhA TQM GdeUHGMs
(3ChdgG (B:s
(3CeG HYO aEf fhY GdCOH Ydi cKQI TLhJg hJTYH afhfg fhY YR Ydi GdWdHI eQGeg hGSJYUi ReGfg aYWT HCfa TGeN hcJHJ ai TQM GdeUHGM cJGHkG LeYJ ajg ef GdbhGYO eG jaJM GdZdb s
(3BNQgG (B:s
(3hgPG HGH ddEWfGH ajg eMGd dcfg jYVi Edi GdedGd aGJUQJ Ydi gPG GdbOQ hdjS GdPi Yf GdbTGa hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3fSNI KGfjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GddZIs